Neuronatin regulates whole‐body metabolism: is thermogenesis involved?. Issue 10 (2nd September 2020) - Braun, Jessica L.; Geromella, Mia S.; Hamstra, Sophie I.; Fajardo, Val A.
Abstract: Neuronatin (NNAT) was originally discovered in 1995 and labeled as a brain developmental gene due to its abundant expression in developing brains. Over the past 25 years, researchers have uncovered NNAT in other tissues; notably, the hypothalamus, pancreatic β‐cells, and adipocytes. Recent evidence in these tissues indicates that NNAT plays a significant role in metabolism whereby it regulates food intake, insulin secretion, and adipocyte differentiation. Furthermore, genetic deletion of Nnat in mice lowers whole‐body energy expenditure and increases susceptibility to diet‐induced obesity and glucose intolerance; however, the underlying cellular mechanisms remain unknown. Based on its sequence homology with phospholamban, NNAT has a purported role in regulating the sarco(endo)plasmic reticulum Ca 2+ ATPase (SERCA) pump. However, NNAT also shares sequence homology with sarcolipin, which has the unique property of uncoupling the SERCA pump, increasing whole‐body energy expenditure and thus promoting adaptive thermogenesis in states of caloric excess or cold exposure. Thus, in this article, we discuss the accumulating evidence suggestive of NNAT's role in whole‐body metabolic regulation, while highlighting its potential to mediate adaptive thermogenesis via SERCA uncoupling.